INCOME DISPARITY AND CORRELATION IN JAPAN. Issue 1 (26th April 2013) - Tamesue, Kazuki; Tsutsumi, Morito; Yamagata, Yoshiki
Abstract With the collapse of the bubble economy in the early 1990s, economic disparities have arisen both among the people and in the different regions of Japan. Advancements in spatial analysis have led to the development of strong tools to explicitly consider spatial dependence and heterogeneity; however, no significant research has been carried out using such tools for analyzing the economic disparity at the municipal level in Japan. The objective of this study is to analyze the regional income disparities in Japan during the period known as the "lost decade." The data used in this research are annual data collected at the municipality level during 1998–2007. Exploratory spatial data analysis and local indicators of spatial association have been used to classify municipalities into categories and to identify local spatial clustering and spatial outliers leading to income disparity in Japan, respectively.